Avelumab expanded access program in metastatic Merkel cell carcinoma: Efficacy and safety findings from patients in Europe and the Middle East. Issue 11 (3rd August 2021) - Ascierto, Paolo Antonio; Orlova, Kristina; Grignani, Giovanni; Dudzisz‐Śledź, Monika; Fenig, Eyal; Chiarion Sileni, Vanna; Fazio, Nicola; Samimi, Mahtab; Mortier, Laurent; Gebhardt, Christoffer; Kramkimel, Nora; Steven, Neil; et al.
Abstract: Incidence rates of Merkel cell carcinoma (MCC), an uncommon skin cancer with an aggressive disease course, have increased in recent decades. Limited treatment options are available for patients with metastatic MCC (mMCC). Avelumab, an anti‐programmed cell death‐ligand 1 monoclonal antibody, became the first approved treatment for mMCC after the results of the phase 2 JAVELIN Merkel 200 study. Prior to its regulatory approval, an expanded access program (EAP) enabled compassionate use of avelumab in patients with mMCC. Here we report findings from patients enrolled in the EAP in Europe and the Middle East. Efficacy and safety data were provided at the discretion of treating physicians. Between March 2, 2016, and December 22, 2018, 403 requests for avelumab were received from 21 countries, and avelumab was supplied to 335 patients. Most patients (96.7%) received avelumab as second‐line or later treatment. In 150 patients for whom response data were available, the objective response rate was 48.0%, and in responding patients, median duration of treatment was 7.4 months (range, 1.0‐41.7 months). The most common treatment‐related adverse events were infusion‐related reaction (2.4%) and pyrexia (2.1%), and no new safety signals were observed. Overall, results from European and Middle Eastern patients enrolled in this EAP confirm the efficacy and safety of avelumab treatment observed in previous studies in patients with mMCC. Abstract : What's new? Patients with the aggressive skin cancer Merkel cell carcinoma (MCC) have few treatment options. The first approved treatment for metastatic MCC, the anti‐PD‐L1 monoclonal antibody avelumab, was made available through an expanded access program (EAP) prior to regulatory approval. Here, the authors analyze data from 150 patients in Europe and the Middle East enrolled in that EAP. Avelumab's efficacy and safety in this real‐world population of patients, they found, confirm the findings reported from the JAVELIN Merkel 200 trial.